On some fundamental integral and finite difference inequalities in three variables - Pachpatte, B.G.
The aim of the present paper is to establish some new integral and finite difference inequalities in three variables which can be used as tools in the analysis of certain new classes of differential, integral and finite difference equations. Some applications to convey the importance of one of our result are also given.
Keywords: Integral and finite difference inequalities; Explicit estimates; Sum-difference equations